2016
DOI: 10.1088/1612-202x/aa4fc0
|View full text |Cite
|
Sign up to set email alerts
|

Laser induced breakdown spectroscopy with picosecond pulse train

Abstract: Picosecond pulse train and nanosecond pulse were compared for laser ablation and laser induced breakdown spectroscopy (LIBS) measurements. A detailed study revealed that the picosecond pulse train ablation improved the quality of laser craters (symmetric crater walls and the absence of large redeposited droplets), which was explained by a smaller heat affected zone and suppression of melt splash. Greater plasma dimensions and brighter plasma emission were observed by gated imaging for picosecond pulse train co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…The fs-plasma evolves and decays much faster than ps/ns-plasmas. , For 500 ns, after the laser strikes the material, ns-plasma kinetic energy is mainly spent in compressing the surrounding air and forming a shock wave. At this stage, the ns-spectrum is dominated by continuum radiation with no information to be collected precisely.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fs-plasma evolves and decays much faster than ps/ns-plasmas. , For 500 ns, after the laser strikes the material, ns-plasma kinetic energy is mainly spent in compressing the surrounding air and forming a shock wave. At this stage, the ns-spectrum is dominated by continuum radiation with no information to be collected precisely.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Commonly, in ns-LIBS, delaying data acquisition with respect to laser firing to avoid the overwhelming continuum radiation and to suppress spectral interference due to line broadening costs ∼1–1.5 μs at optimized experimental configurations. Results reported for a ps-train showed that 700 ns was consumed by continuum emission to reduce to a background emission level . While ps/ns-plasmas’ absorptivity diminishes markedly to change the opacity from optically thick into transparent thin media, the fs-plasma lacks any kind of “plasma shielding” or “laser trail-plasma interaction”, which dominantly makes its evolution a confined and stable event.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Zhang and coauthors [28] determined accuracy, precision, and detection limits of seven elements in steel reference materials by optimizing laser energy, lens-to-sample distance, and delay time. Most recently, a comparative study between picoseconds (ps) and nanosecond (ns) laser pulses for LIBS measurements on steel samples was recently conducted [29]. Better SBRs for several atomic and ionic lines, as well as improved precision and limits of detection for the elements Fe, Cr, and Si were obtained with the ps laser.…”
Section: Introductionmentioning
confidence: 99%
“…Labutin et al [3] summarize nearly two decades of studies on femtosecond laser-induced breakdown spectrometry (fs-LIBS). Picosecond pulse train and nanosecond pulse were compared for laser ablation and LIBS measurements by Lednev et al [4].…”
Section: Introductionmentioning
confidence: 99%